Impact of Participatory forest Management on Socio-economic Development of Rural People: a Case Study in Kodsi and Talaichittor Villages of Dehra Dun District - Gupta, Ranjana; Srivastava, Shivendu K.; Mahendra, A. K.; Pundir, Ira; Kumar, Dinesh (Indian Forester, 2004)
Joint Forest Management or Participatory Forest Management (PFM) got its formal shape in the year 1990. A need has arisen to evaluate the impact of this new management tool. A study was taken up in Kodsi and Talaichittor villages of Dehra Dun District to assess the impact of PFM on the socio-economic development of rural people and to identify the prime ingredients of PFM programme responsible for bringing about the desired changes. It was observed that the household income has considerably increased due to alternative job opportunities, agricultural production has increased, there is reduction in distance travelled and time spent for fuel wood and fodder collection, village women are now financially empowered, and institution building has paved the way for sustainability of the whole process.